DINAMIKA TEMPORAL KOMUNITAS LAMUN PADA MUSIM KEMARAU DI INTERTIDAL MADASANGER, KABUPATEN SUMBAWA BARAT - Tria Khairunnisa; Fredinan Yulianda; Rahmat Kurnia (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Seagrass is one of the communities in the intertidal Madasanger. Due to environmental characteristic, this intertidal area is always dynamic mainly is caused by a change of tidal wave. This condition cause habitat for seagrass living often changes. The aim of this study is to analyzed dynamic community of seagrass on the dry season in Madasanger. Seagrass community was observed at two stations parallel to the coastline, such as high tide zone and low tide zone during dry season (April). The seagrass community distributed dynamically based on percent cover and spatial pattern. There are five genera of seagrass such as Cymodocea, Halodule, Halophila, Syringodium, and Thalassia cover the habitat with 36.5-75.67%. During period 2014-2018, the highest percent cover of seagrass was found in 2016. This condition in 2016 is the best environment for seagrass living because of limiting rainfall (input of freshwater). The seagrass habitat lived better mainly Halodule and Syringodium in deeper substrate. The dynamic of seagrass community intertidal Madasanger showed by the sand movement follow up with the changes of seagrass spatial distribution during five years.